Group Guidance with Role Play Techniques to Improve the Students’ Interpersonal Communication (Jurnal Bimbingan Konseling, 2018)
This research aims to describe the role-playing technique group guidance services that improve interpersonal communication effectively in grade XI science students of SMA Bhinneka Karya 6 Boyolali. Experimental research method, using the design of one group pre-test post-test with research subjects of class XI IPA 1 as many as 25 students selected by purposive sampling technique. Based on the results of the t-test analysis it can be understood that the improvement of interpersonal communication between before and after being given group guidance services with role-play techniques (t(10) = 9.73, p < 0.01). This finding confirms that group guidance with role-playing techniques can be applied to improve student interpersonal communication